Effect of Pilot and Air Traffic Control Experiences and Automation Management Strategies on Unmanned Aircraft Systems Mission Task Performance. Issue 5 (11th October 2011) - Liu, Dahai; Reynolds, Christopher; Vincenzi, Dennis; Doherty, Shawn
Abstract The demand for Unmanned Aircraft Systems (UASs) capabilities is rapidly increasing in the civilian sector. UAS operations, however, will not be carried out in the National Airspace System until safety concerns are alleviated. Among these concerns is determining the appropriate level of automation in conjunction with a suitable pilot who exhibits the necessary knowledge, skills, and abilities to safely operate these systems. This research examined two levels of automation: management by consent (MBC) and management by exception (MBE), in conjunction with pilot experiences while operating an unmanned aircraft simulator. The user experiences encompass three individual groups: pilots, air traffic controllers (ATC), and non‐pilot/non‐ATCs. Performance, workload, and situational awareness data were examined. Results show no significant differences among pilot experiences groups, automation strategies, or the interaction between these two. Limitations and design implications are discussed to help pave the way for future research. © 2011 Wiley Periodicals, Inc.